2002
DOI: 10.1007/s00345-001-0238-z
|View full text |Cite
|
Sign up to set email alerts
|

Increase in detrusor wall thickness indicates bladder outlet obstruction (BOO) in men

Abstract: Detrusor wall thickness decreases continuously while the bladder fills to 50% of its capacity and then remains constant until 100%. Therefore, detrusor wall measurements were performed in patients when the bladder was filled to maximum capacity only. Mean detrusor wall thickness for unobstructed (n = 14), equivocal (n=23) and obstructed patients (n=33) were 1.33, 1.62 and 2.4 mm, respectively (P <0.001). With increasing CHESS letters and CHESS numbers, the thickness of the detrusor wall increased as well (P< 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
2
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 0 publications
10
120
2
7
Order By: Relevance
“…Uroflowmetry was assessed in 2580 patients across 16 studies. Thirteen studies used a cutoff value of 10 ml/s to diagnose BOO and reported median sensitivity of 68.3%, specificity of 70.5%, a PPV of 74.3% and NPV of 68% [7,12,13,15,16,18,20,21,26,30,33,34,38,40,41]. However, studies varied considerably in their choice of defining variable and cutoff values.…”
Section: Diagnostic Accuracy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uroflowmetry was assessed in 2580 patients across 16 studies. Thirteen studies used a cutoff value of 10 ml/s to diagnose BOO and reported median sensitivity of 68.3%, specificity of 70.5%, a PPV of 74.3% and NPV of 68% [7,12,13,15,16,18,20,21,26,30,33,34,38,40,41]. However, studies varied considerably in their choice of defining variable and cutoff values.…”
Section: Diagnostic Accuracy Resultsmentioning
confidence: 99%
“…DWT/BWT. DWT was studied in 848 patients across eight studies [6,8,16,17,24,31,33,34], five of which used a cutoff of 2 mm to define BOO, with high median sensitivity of 82.7%, specificity of 92.6%, a PPV of 90.5%, and NPV of 85%. Furthermore, a well-conducted exploratory study reported a cutoff value of 2.9 mm as having the best diagnostic value, with specificity of 100%.…”
Section: Diagnostic Accuracy Resultsmentioning
confidence: 99%
“…LUTS were classified according to the IPSS as minimal (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe ( > 20). The duration of LUTS was also recorded .…”
Section: Methodsmentioning
confidence: 99%
“…The bladder wall thickness (BWT) was also determined by abdominal US using a baseline bladder capacity of 60% (i.e. 150-200 mL) with values of > 2 mm being considered abnormal [12]. All patients had a detailed medical history taken, a physical examination and urine analysis, with laboratory blood tests.…”
Section: Methodsmentioning
confidence: 99%
“…Our data showed estrogen-induced urothelial cell proliferation both in vivo and in vitro. In contrast to the muscle cell hyperplasia frequently observed in BOO, 40,41 the detrusor in AROMϩ/6J mice undergoes atrophy at 10 months of age. Similarly to AROMϩ/N males, 29,35 the AROMϩ/6J males showed high serum E 2 and low testosterone levels, decreased androgen/estrogen ratio, and disrupted reproductive development and spermatogenesis, putatively due to estrogen susceptibility of the C57Bl/6J genetic background.…”
Section: Discussionmentioning
confidence: 61%